2016
DOI: 10.3389/fnins.2016.00340
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of Tourette Syndrome and Attention Deficit Hyperactivity Disorder Provides Support for a Shared Genetic Basis

Abstract: Gilles de la Tourette Sydrome (TS) is a childhood onset neurodevelopmental disorder, characterized phenotypically by the presence of multiple motor and vocal tics. It is often accompanied by multiple psychiatric comorbidities, with Attention Deficit/Hyperactivity Disorder (ADHD) among the most common. The extensive co-occurrence of the two disorders suggests a shared genetic background. A major step toward the elucidation of the genetic architecture of TS was undertaken by the first TS Genome-wide Association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
(42 reference statements)
3
15
0
Order By: Relevance
“…Similar effects of young parental age on both ADHD and TS/CT are in line with previously recorded shared etiological pathways for these disorders -including both genetic 34,35 and environmental 36,37 risk factors -and frequent co-occurrences observed between these conditions. 38 However, given co-morbidity between ADHD, TS/CT and OCD 38 it was of interest that young age at child's birth had opposite effects on the risk for those disorders.…”
Section: The Role Of Parental Age In Asd Adhd Ocd and Ts/ctsupporting
confidence: 89%
“…Similar effects of young parental age on both ADHD and TS/CT are in line with previously recorded shared etiological pathways for these disorders -including both genetic 34,35 and environmental 36,37 risk factors -and frequent co-occurrences observed between these conditions. 38 However, given co-morbidity between ADHD, TS/CT and OCD 38 it was of interest that young age at child's birth had opposite effects on the risk for those disorders.…”
Section: The Role Of Parental Age In Asd Adhd Ocd and Ts/ctsupporting
confidence: 89%
“…Still one PRS study (4) and three heritability studies suggested a shared genetic background between TS and OCD (6,14,31). Little is known about the possible genetic overlap between TS and ADHD, with one PRS study agreeing with our finding of no overlap (4) and two heritability studies (14,32) suggesting overlap. Lastly, consistent with our findings, Anttila et al (14) did not find evidence for shared genetic risk factors between TS and ASD.…”
Section: Discussionsupporting
confidence: 57%
“…(d) 12 TS GWAS-based top SNPs, i.e., the top 5 LD-independent SNPs from the first GWAS of TS [ 6 ], 4 top SNPs from the Gilles de la Tourette Syndrome Genome-Wide Association Study Replication Initiative [ 7 ], and the top 3 SNPs from the first cross-disorder GWAS of TS and OCD [ 20 ]; and (e) 17 top SNPs from GWAS studies of OCD [ 21 ], ADHD [ 22 , 23 ], and ASD [ 24 , 25 ]. We did not include the previously implicated TS SNPs rs1894236 ( HDC ), rs1056534 ( TBCD ), rs25531 ( SLC6A4 ), rs25532 ( SLC6A4 ), nor tSNPs covering the possible TS candidate genes DRD4 , Arylacetamide Deacetylase ( AADAC ) [ 26 , 27 ], and Glial Cell Derived Neurotrophic Factor ( GDNF ) [ 27 ], nor 19 SNPs recently implicated in a meta-analysis of TS and ADHD [ 28 ].…”
Section: Methodsmentioning
confidence: 99%